2017
DOI: 10.1063/1.4995527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a static inhomogeneous magnetic field acting on a laser-produced carbon plasma plume

Abstract: On the mechanism of carbon nanostructures formation at reaction of organic compounds at high pressure and temperature AIP Advances 7, 085101 (2017); https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Indeed, it has been reported that the confined plume can enhance the rate of collisional excitation and the corresponding emission. [32][33][34] Hence, the enhancement of the emission intensity and the longer lifetime in a plume can be interpreted as a consequence of the confinement of the plume by the presence of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been reported that the confined plume can enhance the rate of collisional excitation and the corresponding emission. [32][33][34] Hence, the enhancement of the emission intensity and the longer lifetime in a plume can be interpreted as a consequence of the confinement of the plume by the presence of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%